Roles of informal digital learning of English in developing an EFL teacher’s English proficiency - Arief Eko Priyo Atmojo (Research And Innovation In Language Learning (RILL), 2022)
This study sheds light on how IDLE activities play role in developing an Indonesian in-service EFL teacher’s English proficiency. This study employed qualitative approach. One female in-service EFL teacher was purposively selected to become the participant. Data were garnered by written reflections and semi-structured interviews. The credibility of the data was achieved by employing the principles of data saturation. Qualitative coding was then used to analyze the data. To ensure the trustworthiness of the results, the analysis was repeated thrice at different times. The results indicate that both the quality of IDLE activities and the quantity of IDLE activities were important to develop English proficiency although receptive activities were still the most dominant. It was good to undertake IDLE activities on a daily basis. Several tools and resources were also needed to carry out IDLE activities such as gadgets, internet connection, applications, e-books, e-newspapers, as well as online reading and listening materials. Multimodal input such as visualization, lyrics, subtitles, and audio in IDLE activities was really helpful. It was also revealed that the underlying advantages of IDLE activities included providing language exposure, creating English environment, increasing confidence to use English, entertaining, having lots of free resources, as well as being flexible to be undertaken anytime and anywhere. Moreover, IDLE activities could enhance many language aspects such as pronunciation, vocabulary, grammar, conversational skill, writing skill, speaking skill, and listening skill. Future studies on IDLE are encouraged and directed